FROM DIGITAL PROFICIENCY TO COMMUNICATIVE CONFIDENCE: THE MEDIATING ROLE OF ATTITUDES IN AI-ASSISTED LANGUAGE LEARNING - Lalita Vistari; Issy Yuliasri; Yuliati (University of Kuningan, 2026)
Artificial Intelligence (AI) is an influential factor in improving the speaking and communication skills of students in language learning. And yet, there is a knowledge gap in relation to students’ self-reported readiness levels for communication vis-à-vis their prediction on preparedness for AI-assisted digital learning, alongside their technological literacy and attitudes towards AI. The present study uses TAM for the context of digital learning and adopts a quantitative approach with a correlation research design using SEM. The subjects of the study were English education students in Indonesia, and several aspects, such as Technology readiness, Attitudes towards AI, & Communicative readiness, were measured using a structured questionnaire. The results highlighted the statistically significant direct and indirect links of technology readiness with positive AI attitudes, as well as communicative readiness. The standardized path estimates showed that students with high technical skills and strong attitudes towards the AI tool reported more communication-enhanced confidence. AI communication tools can contribute to the development of students’ communicative competence, but they are not simply a reflection of some specific purpose without emotional and cognitive engagement between learners and AI products. This research offers novelty by integrating TAM and TRI to test the mediation of attitudes towards AI on the communicative readiness of English language education students in Indonesia, filling an empirical gap in developing countries. State of the art highlights AI development, such as chatbots in Southeast Asia, but there is little exploration of the emotional roles and local infrastructure, which is completed by this validated SEM model. Yet, this study suggests that attention to students’ perceptions and readiness, including how they perceive ICT in their social networks and are ready for using ICT for learning, is a key factor to enhance digital learning environments. This study adds to this work by showing AI-enhanced technology can productively augment communicative competence when students are well-prepared and motivated.